Broad-range TRP channel inhibitors (2-APB, flufenamic acid, SKF-96365) affect differently contraction of resistance and conduit femoral arteries of rat - Bencze, Michal; Behuliak, Michal; Vavřínová, Anna; Zicha, Josef (European journal of pharmacology, 2015)
Transient receptor potential (TRP) channels are proposed to contribute to membrane depolarization and Ca2+ influx into vascular smooth muscle (VSM) cells. Our aim was to study the effects of widely used broad-range TRP channel inhibitors--2-aminoethoxydiphenyl borate (2-APB), flufenamic acid (FFA) and SKF-96365--on the contraction of freshly isolated small and large arteries. Endothelium-denuded resistance (≈250 µm) and conduit (≈1000 µm) femoral arteries were isolated from adult Wistar rats and mounted in wire myograph. The effects of the above mentioned TRP channel inhibitors and voltage-dependent calcium channel inhibitor nifedipine were studied on arterial contractions induced by phenylephrine, U-46619 or K+. Phenylephrine-induced contractions were also studied in the absence of extracellular Na+. mRNA expression of particular canonical and melastatin TRP channel subunits in femoral vascular bed was determined. TRP channel inhibitors attenuated K+-induced contraction less than nifedipine. Phenylephrine-induced contraction was more influenced by 2-APB in resistance arteries, while FFA completely prevented U-46619-induced contraction in both sizes of arteries. The absence of extracellular Na+ prevented the inhibitory effects of 2-APB, but not those of FFA. The observed effects of broad-range TRP channel inhibitors, which were dependent on the size of the artery, confirmed the involvement of TRP channels in agonist-induced contractions. The inhibitory effects of 2-APB (but not those of FFA or SKF-96365) were dependent on the presence of extracellular Na+.
Keywords: Imidazoles; arteria femoralis; kyselina flufenamová; Muscle, Smooth, Vascular; Male; Rats, Wistar; orgánové kultury - kultivační techniky; Flufenamic acid; TRP channel; imidazoly; 2-APB; Femoral Artery; vztah mezi dávkou a účinkem léčiva; kationtové kanály TRP; mužské pohlaví; Transient Receptor Potential Channels; potkani Wistar; Organ Culture Techniques; Vasoconstriction; krysa rodu Rattus; Animals; svaly hladké cévní; Flufenamic Acid; zvířata; Rats; vazokonstrikce; SKF-96365; sloučeniny boru; Boron Compounds; Vascular contraction; Dose-Response Relationship, Drug; Femoral artery